2006
DOI: 10.1021/ic0607235
|View full text |Cite
|
Sign up to set email alerts
|

Oxo- and Oxoperoxo-molybdenum(VI) Complexes with Aryl Hydroxamates:  Synthesis, Structure, and Catalytic Uses in Highly Efficient, Selective, and Ecologically Benign Peroxidic Epoxidation of Olefins

Abstract: A solution obtained by dissolving MoO3 in H2O2 reacts separately with secondary hydroxamic acids (viz., N-benzoyl N-phenyl hydroxamic acid (BPHAH), N-benzoyl N-ortho-, -meta-, -para-tolyl hydroxamic acids, (BOTHAH, BMTHAH, and BPTHAH, respectively), and N-cinnamoyl N-phenyl hydroxamic acid (CPHAH) affording [MoO(O2)(BPHA)2] (1), [MoO(O2)(BOTHA)2] (2), [MoO(O2)(BMTHA)2] (3), [MoO(O2)(BPTHA)2] (4), and [Mo(O)2(CPHA)2](5), respectively. The O and O2 are situated cis to each other in 2-4, but in each case, they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…As part of our continued interest in using oxoperoxomolybdenum complexes as oxidation catalysts, we were intrigued by previous reports [26,27] at the failure of the Mo-complexes to activate H 2 O 2 and by using a molybdenum complex, PPh 4 [MoO(O 2 ) 2 (SaloxH)] [6] (SaloxH 2 = Salicylaldoxime) as catalyst along with NaH CO 3 as cocatalyst [28,29] we were able to activate H 2 O 2 and the integrated catalyst, co-catalyst and oxidant functioned as a very efficient peroxidic epoxidation system. Inspired by this result, we reported some other peroxo complexes, which showed higher to much higher catalytic efficiencies [6][7][8][9][10] for olefin epoxidation. In this paper, we report the synthesis, structural characterization, and catalytic epoxidation activities of two oxodiperoxo complexes, [MoO(O 2 ) 2 (PyCOXH) (H 2 O)] (1) (PyCOXH = Pyridine-2-carboxaldoxime) and PMePh 3 [MoO(O 2 ) 2 (PyCO)] (2) (PyCOH = Pyridine-2-carboxylic acid).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…As part of our continued interest in using oxoperoxomolybdenum complexes as oxidation catalysts, we were intrigued by previous reports [26,27] at the failure of the Mo-complexes to activate H 2 O 2 and by using a molybdenum complex, PPh 4 [MoO(O 2 ) 2 (SaloxH)] [6] (SaloxH 2 = Salicylaldoxime) as catalyst along with NaH CO 3 as cocatalyst [28,29] we were able to activate H 2 O 2 and the integrated catalyst, co-catalyst and oxidant functioned as a very efficient peroxidic epoxidation system. Inspired by this result, we reported some other peroxo complexes, which showed higher to much higher catalytic efficiencies [6][7][8][9][10] for olefin epoxidation. In this paper, we report the synthesis, structural characterization, and catalytic epoxidation activities of two oxodiperoxo complexes, [MoO(O 2 ) 2 (PyCOXH) (H 2 O)] (1) (PyCOXH = Pyridine-2-carboxaldoxime) and PMePh 3 [MoO(O 2 ) 2 (PyCO)] (2) (PyCOH = Pyridine-2-carboxylic acid).…”
Section: Introductionmentioning
confidence: 72%
“…[6,8,9]) showed that the oximate ligands coordinated to MO(O 2 ) 2 (M = Mo or W) moiety produced complexes, which were more potential epoxidation-catalyst than the corresponding carboxylate ligands attached to the same moiety. In this work, we find a reverse situation by observing that 2 is a more potential catalyst than 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is cheap, readily available and gives water as the only by-product [15]. Molybdenum and tungsten complexes have been widely investigated because of their demonstrated high activity for selective oxidation with TBHP [16][17][18][19][20] and H 2 O 2 [21][22][23][24][25][26][27][28]. However, to the best of our knowledge, the catalytic performance of Mo(II) and W(II) carbonyl compounds in olefin epoxidation using H 2 O 2 has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Of the many ways to accomplish alkene epoxidation using transition metal complexes as catalysts [2][3][4][5][6][7], H 2 O 2 is probably the best ecologically sustainable ''green'' terminal oxidant [8], after dioxygen. Quite a few reports have already appeared in the area of homogeneous catalytic epoxidation with hydrogen peroxide as oxidant and a variety of transition metal complexes as catalysts [3,[9][10][11][12][13][14][15][16][17][18][19][20]. In the oxodiperoxo chemistry of molybdenum and tungsten, it has already been shown that the MO(O 2 ) 2 (M = Mo or W) cores, when bound to one bidentate or two unidentate ligands, afford complexes that are useful catalysts in the epoxidation of alkenes [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%